Psychological health of mothers and siblings of children with autism spectrum disorders during COVID-19 pandemic: new evidence in Italian families - Camia, Michela; Scorza, Maristella; Lipparini, Andrea; Martorana, Lorelay; Nardocci, Franco; Padovani, Roberto; Rubichi, Sandro; Benassi, Erika (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Psychological challenges are well recognized in families with a child with Autism Spectrum Disorders (ASD). Instead, less is known about the effects of traumatic scenarios, such as COVID-19, on the psychological health of these families. The main aim of this research was to study the psychological health of both mothers and typically developing (TD) siblings of children with ASD during the COVID-19 pandemic. Second, we investigated the relationship between the mothers’ psychological resources and their children psychological well-being.Methods: The sample included 52 mothers and their children: 15 with one child with ASD and at least one TD child (aged 4-14) (ASD-siblings group) and 37 with one or more TD child (aged 4-14) (TD control group). The data were collected through an online platform; four standardized questionnaires (GAD-7, BDI-II, CD-RISC 25 and CBCL) were administered. Results: The analyses revealed more internalizing and total behavioral symptoms in the siblings of children with ASD, compared to TD control group. Regarding the mothers, we did not find differences in depression and anxious symptoms between the two groups. However, the results reported a lower level of resilience in the mothers of children with ASD relative to mothers of TD children. Finally, the psychological well-being of the TD children was associated with the level of mothers’ anxiety only in the ASD-siblings group. Conclusions: Overall, our data show that the COVID-19 outbreak may had been particularly challenging for families of children with ASD, and highlight the importance of intensifying psychological support to families.